Comparison of phenylpropanoid metabolism of three physiological disorders in apple and pear - Linru Wang; Gengsen Liu; Lianmei Liu; Yugang Zhang; Haiyong Qu (Horticultural Science)
Apples and pears are the main temperate fruit tree species, and metabolic disorders may occur during their development and post-harvest storage periods, leading to physiological diseases. In this study, we detected the phenylalanine ammonia-lyase (PAL) enzyme and related metabolites involved in phenylpropanoid metabolism in the pulp of pear with hard-end or cork spot and in the pulp of apple with bitter pit. These three physiological disorders differed in phenylpropanoid metabolism and had similar PAL activity, but their polyphenol, flavonoid, and lignin contents changes were completely. For fruits with the three types of physiological metabolic disorders, the auxin content in the tissues with metabolic disorder symptoms was higher than that in the healthy tissues. In summary, the three physiological disorders showed similar changes in the activities of key enzymes (i.e., PAL) involved in phenylpropane metabolism, but their metabolites significantly differed.